TAWHID IS THE TRUE BASIS FOR EPISTEMOLOGY - Keith Morrison (Sadra International Institute, 2023)
There is a common sense of urgency among Islamic and Eastern Orthodox Christian scholars to reestablish a proper ground for intellectual work. This paper argues that tawhid provides the proper ground, because it describes the universe as a hypostatic unity. Humans are made in the image of God as a microcosm of the universe, called to fulfill the unifying movement of tawhid, by bringing the universe into awareness of the Creator. Tawhid therefore provides a universal basis for appreciating all cultural streams and disciplines, as expressing rainbow-like, unique colours of universal genius. The unifying of the rainbow of genius is itself part of tawhid. The rise of modern Western epistemology is one particular genius. Unfortunately modern Western epistemology appears to have confused universal with global, and forgotten that it is only part of the rainbow. It has lost sight of the context of tawhid. In particular it has lost sight of the priority of quality over quantity. It limits itself to secondary or extrinsic social constructed essences for abstraction of utility. The reifying of socially constructed and technologically enhanced secondary qualities as amounts of substance, which can be controlled through abstract causality within a force field, is used to justify attempted global dominance through a misplaced ontology of subliminal violence. The true cause, which hypostatically, graciously and compassionate gifts unique qualities, known through illumination mediated by angels, as beings moving in divine harmony and divine beauty toward tawhid, has been lost sight of. A recovery of the context of tawhid is the unifying movement of: gaining virtues through overcoming injustice; overcoming unsustainable interactions with other creatures; contemplating illumination from angels whilst rejecting temptations from demons; all to become into the likeness of God through doing God’s will to fulfill creation as a unifying mediator for tawhid